Combination of microscopic techniques reveals a comprehensive visual impression of biofilm structure and composition - Alhede, Morten (2013)
Bacterial biofilms are imaged by various kinds of microscopy including confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). One limitation of CLSM is its restricted magnification, which is resolved by the use of SEM that provides high-magnification spatial images of how the single bacteria are located and interact within the biofilm. However, conventional SEM is limited by the requirement of dehydration of the samples during preparation. As biofilms consist mainly of water, the specimen dehydration might alter its morphology. High magnification yet authentic images are important to understand the physiology of biofilms. We compared conventional SEM, Focused Ion Beam (FIB)-SEM and CLSM with SEM techniques [cryo-SEM and environmental-SEM (ESEM)] that do not require dehydration. In the case of cryo-SEM, the biofilm is not dehydrated but kept frozen to obtain high-magnification images closer to the native state of the sample. Using the ESEM technique, no preparation is needed. Applying these methods to biofilms of Pseudomonas aeruginosa showed us that the dehydration of biofilms substantially influences its appearance and that a more authentic biofilm image emerges when combining all methods.